The role of digital marketing tools in promoting tourism: An applied study on online marketing strategies - Abdelrehim Awad; Bshair Alharthi (Innovative Marketing)
Digital marketing has become a central driver in tourism promotion, reshaping how destinations engage with potential visitors. This study investigates the impact of digital marketing strategies ‒ social media marketing, electronic word-of-mouth (e-WOM), and online advertising ‒ on brand awareness and tourists’ intention to visit destinations in Saudi Arabia’s Asir region. The study utilized a sample size of 400 participants, with a 70% response rate, resulting in 280 completed surveys. The sample represented a diverse demographic, with 57.1% male, 42.9% female, 89.3% Saudi nationals, and 96.4% domestic tourists. Data were collected from tourists visiting key attractions such as the Al-Soudah Mountains and Abha, either in person or via digital channels. The survey assessed the effectiveness of digital marketing tools and their influence on brand awareness, intention to visit, and tourist satisfaction.The results analyzed using descriptive statistics, correlation analysis, and multiple regression, revealed that all three digital marketing strategies significantly influenced both brand awareness and the intention to visit. Social media marketing showed the strongest impact (β = 0.31**, p < 0.01), followed by online advertising (β = 0.30**, p < 0.01) and e-WOM (β = 0.25**, p < 0.01). These findings highlight the effectiveness of digital marketing in shaping tourist behavior and decision-making, with significant implications for tourism marketing in emerging destinations like Asir. AcknowledgmentThe authors are thankful to the Deanship of Graduate Studies and Scientific Research at University of Bisha for supporting this work through the Fast-Track Research Support Program.